Clinical acceptability of PEEK fixed dental prosthesis in partially edentulous patient - A one year single arm pilot study - D. Arun Raj; Naveen Gopi Chander; Jetti Ramesh Reddy; Muthukumar Balasubramaniam (Elsevier, 2020)
Purpose: The study evaluated the clinical efficacy of Polyether ether ketone (PEEK) fixed dental prosthesis (FDP) over a period of one year using modified Ryges criteria and California Dental Assessment system. Methods: The group consisted of 20 patients restored with posterior three-unit PEEK FDP. Patient recall and clinical examination of the restorations were done at interval of 0, 3, 6, 9 and 12 months. Clinical examination for evaluation of longevity of restorations was done using modified Ryges criteria and California dental assessment system on chipping of the veneered composite, discoloration at the marginal areas, and marginal adaptation, retention, periodontal health and hygiene of PEEK FDP. Radiographic assessment was done after 12 months. Statistical analysis were done using Friedman test. Results: 95% of the patients had maintained the restoration of PEEK FDP without fracture during the study period. 5% patient reported with de-cementation of fixed dental prosthesis. 10% of the PEEK FDP shows marginal discoloration. However, no significant changes were observed during the periodic time interval evaluation in marginal adaptation, oral hygiene status and periodontal health. (p < 0.5). Conclusion: PEEK FDP had satisfactory clinical efficacy and acceptable clinical outcome during the observation period of 12 months. No significant radiological changes were observed at the end of 12 months.